Residents’ attitudes toward refugee integration: The role of shared identity and refugees’ perceived openness to novel experiences - Judith Knausenberger; Jens H. Hellmann; Gerald Echterhoff (Current Research in Ecological and Social Psychology, 2023)
Refugees often have little control over the circumstances of migration, including their destination country. Receiving-society residents may thus perceive that refugees have relatively low interest in the host culture, resulting in skepticism towards refugee integration. In five studies conducted with German residents (total N = 866), we examined ways to overcome such perceptions via a vignette-based manipulation of a refugee's ostensible openness and social identity. Overall, participants with a more right-wing political orientation exhibited more positive attitudes toward refugee integration and greater willingness to help after reading about a (female) refugee who was (vs. was not) open to experience and who shared (vs. did not share) a key aspect of their identity, namely being a student (Studies 1 and 2a) or fan of the same soccer club (Study 4). For a male refugee, these effects did not emerge (Study 2b). In Study 3, non-student participants reported less willingness to help when a student (vs. non-student) refugee was open (vs. not open) to experience. For desire for integration and willingness to help, meta-analytic syntheses revealed robust effect sizes for the three-way interaction between openness, shared identity, and political orientation. Thus, residents’ attitudes toward refugee integration and helping intentions were shaped by refugees’ perceived personality (openness), residents’ political orientation, and by residents’ and refugees’ shared identity.